Differential diagnosis of reactive and septic arthrititides with help of the method of phasometry of human synovial fluid - Kvasniuk, Dmytro; Vasiuk, Sergey; Ushenko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The method of synovial fluid phasometry for differential diagnosis of pathological states in the knee joint was assessed and an algorithm of the research was developed. The study involved 30 patients; of them, pyogenic arthritis of the knee joint was diagnosed in 10 cases, and synovitis with deforming arthrosis of degrees II-III in 20 ones. Results of the research indicate that there are reliable differences between values of statistic moments of orders 1-4 in two groups, thereby making it possible to objectively differentiate the above knee joint pathology very quickly.